2021
DOI: 10.1155/2021/8557690
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Data Processing Software for Internet of Things Based on Virtual Reality

Abstract: With the rapid development of the times, the application of the Internet of Things also develops rapidly, resulting in a linear increase in the data generated by the application. Nowadays, people’s needs for the forms and types of data are becoming more and more diversified, and the demand for the analysis and processing of Internet of Things data is only increasing. In order to meet the demand for data analysis of the Internet of Things, this article mainly introduces the design and implementation of the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…To mitigate the limitations of complex transformer models [27][28][29][30], recent studies [31][32][33][34] have shown that good performance can still be achieved by replacing attention-based modules in transformer models with an MLP. This is because both the MLP (e.g., two fully connected layer networks) and the attention mechanism are information processing units.…”
Section: Mlp In Computer Visionmentioning
confidence: 99%
“…To mitigate the limitations of complex transformer models [27][28][29][30], recent studies [31][32][33][34] have shown that good performance can still be achieved by replacing attention-based modules in transformer models with an MLP. This is because both the MLP (e.g., two fully connected layer networks) and the attention mechanism are information processing units.…”
Section: Mlp In Computer Visionmentioning
confidence: 99%